Obligation, Face and Facework: An Empirical Study of the Communicative Act of Cancellation of an Obligation by Chinese, Danish and British Business Professionals in Both L1 and ELF Contexts - Xia Zhang (Copenhagen Business School (CBS), 2019)
This study investigates an under-researched complex communicative act called “cancellation of an obligation”, produced by Chinese, Danish and British business professionals in both L1 and ELF contexts. It is embedded in an implicitly meta-interactional context consisting of a speaker's request, a hearer's promise and the speaker's cancellation. The data were extracted from the GEBCom speech production corpus, which used the closed role play method at the offices of Carlsberg Group in China, Denmark and the UK. The selected data comprise 354 oral responses by 121 respondents in one turn of telephone conversation in three social situations involving cancellation of an obligation (Moving Scenario, Meeting Scenario and Lunch Scenario). Focusing on these three scenarios, I investigate the following research questions: (1) What are the similarities and differences in the way in which Danish and Chinese business professionals keep face and maintain interpersonal harmony in the communicative situations of cancellation of an obligation in their respective L1s? Why do these similarities and differences occur? (2) What are the similarities and differences in the way in which the non-native Danish and Chinese professional business ELF users keep face and maintain interpersonal harmony in the same communicative situations as compared with native British professionals? Why do these similarities and differences occur? (3) To what extent are prototypical facework strategies transferred from L1 communication to ELF communication? All the research questions are united under the overarching theme of exploring the communication challenges of using English as a lingua franca in the Danish-Chinese business communication context. An integrated discourse-pragmatic approach was adopted to analyse the data, focusing on the linguistic realisation patterns and the attitudes, as well as the metainteractional context. A new integrated conceptual framework was developed.
hdl:10398/9726
Keywords: 650